NON-OBSERVANCE OF MAXIMS AND THE IMPLICATURE IN SHANG-CHI MOVIE (Jurnal Bahasa Lingua Scientia, 2023)
Being fluent in a particular language is beneficial for everyone in many aspects. The conversation is beyond just being fluent in languages. According to Grice (1975), the effectiveness of conversation relies on the cooperative principle, which involves participants making efforts to contribute relevant and informative messages and it is essential. However, the speaker often does not fulfill the maxim in conversation whether it is consciously or unconsciously due to various factors. This study aims to investigate the non-observance of maxim and the implicature in Shang-Chi and The Legend of The Ten Rings movie. According to Grice (1975), there are 4 types of non-observance of maxims: flouting, violating, opting out, and infringing the maxim. Thomas (2013) proposed another type of non-observance of the maxim which is suspending the maxim. Moreover, the non-observance of the maxims is result in implicature. This research is analysed by using the qualitative descriptive design. The data of this research is the utterances of the characters. The result of this research shows that the characters do not observe the maxim by dominantly flouting the maxim with 24 occurrences, then followed by violating the maxim with 12 occurrences, opting out with 5 times occurrences, and the last one is infringing the maxim with 4 times occurrences. The characters use implicature often to get what they want without looking desperate to get it, protect their ego, be polite in expressing their opinion and desire, emphasize a point without appearing impolite or assertive, and skilfully guide others to believe what they said and command other through indirect suggestions.
Keywords: Non-observance of maxim; Implicature; Pragmatic